On the Logical Form of Evidential Conditionals - Rott, Hans (Logic and Logical Philosophy, 2023)
The dominant analyses of the logical form of natural-language conditionals take them to be “suppositional conditionals”. The latter are true or accepted if the consequent is true/accepted on the supposition of the antecedent. But this can happen although the antecedent is completely irrelevant (or even somewhat adverse) to the consequent. In natural-language conditionals, however, the antecedent is typically meant to support or be evidence for the consequent. The logical form of conditionals will thus be more complex than the suppositional theory would have it. Recently some suggestions as to what this logical form might look like have been made. In this paper, I critically discuss Vincenzo Crupi and Andrea Iacona’s account of “evidential conditionals”, including its recent amendments.